The Influence of Brand Ambassador, Brand Image and Halal Label on Purchasing Decisions on Scarlett Whitening Products - Rindiani Rindiani; Dewi Komala Sari; Kumara Adji Kusuma (Indonesian Interdisciplinary Journal of Sharia Economics)
This study aims to determine the effect of brand ambassadors, brand image, and halal labels on purchasing decisions for Scarlett Whitening. This study aims to analyze the effect of brand ambassadors, brand image, and halal labels on purchasing decisions for Scarlett Whitening products. This study employs a quantitative approach with a population of Sidoarjo residents who have purchased Scarlett Whitening products and are over 17 years old. Samples were taken using a non-probability sampling method with a purposive sampling technique. Data collection was carried out through distributing questionnaires, where respondents' answers were measured using a Likert scale. The results of this study prove that Brand Ambassador has an effect on purchasing decisions on Scarlett Whitening products. In addition, Brand Image affects purchasing decisions on Scarlett whitening products, and the Halal label also influences these decisions.